Is Early Compression Therapy after Perforator Flap Safe and Reliable? - Suh, Hyunsuk Peter; Jeong, Hyung Hwa; Hong, Joon Pio Jp (Journal of Reconstructive Microsurgery, 2019)
Background Due to the concern of circulation compromise, many surgeons hesitate to dangle or challenge the flap in the early postoperative phase. In our experience, early compression may have advantages such as collapse of dead space, evacuation of hematoma, reduction of edema, and stabilization of flap when ambulating. In this study, the effect of early compression of flaps with regard to flap physiology and outcome is evaluated.Methods From postoperative day 3 to 5, a custom-made compression garment was fitted aiming to compress with a pressure of 30 to 35 mmHg. A total of 52 patients (52 flaps) were enrolled for the study and 48 flaps underwent early compression. The compression was applied not only over the flap but also over the extremity or trunk. The flap outcome as well as flow velocity and flow volume of the pedicle before and after compression was measured and evaluated.Results There was no flap complication during the early compression and early ambulation. And, there was no statistical difference either in the flow velocity or in the volume before and after the compression therapy (29.21 vs. 29.42 cm/s and 7.13 vs. 6.56 cm3/s, respectively).Conclusion Early compression with a 30-mmHg pressure customized pressure garment after the flap surgery does not affect the hemodynamics of the perforator and can be safely used after extremity reconstruction before ambulation.
Keywords: perforator flap; compression of flaps; flap surgery